Evaluation Of Hepatoprotective Effect Of Dietary Inclusion Of Ficus Glomerata Fruits Against Cisplatin-Induced Hepatic Damage In Rats (Journal of Pharmaceutical Negative Results, 2022)
In the present study, cisplatin-induced liver impairment was evidenced by an increase in serum ALT, ALP, and AST and hepatocytecell degeneration, inflammatory infiltrate, and necrosis. These changes persisted on the 6th day due to a single dose of 6 mg/kg cisplatin.The 2% and 4% of Ficus glomerata normalized serum ALT, ALP, AST, LOD, GSH, SOD, and catalase of the liver. The researchersreported that cisplatin administration induced a significant increase in serum ALT, AST, and ALP and a significant decrease in serumtotal bilirubin, total protein, and albumin levels. The ability of cisplatin to cause alterations in the activity of these enzymes could be asecondary event following Cisplatin-induced liver damage with the consequent leakage from hepatocytes. The present study revealedthat significantly decreased levels of ALT, ALP, and AST in blood serum due to their antioxidant effects and their ability to act as freeradical scavengers, thereby protecting membrane permeability after treatment with 2% and 4% of Ficus glomerata indicatehepatoprotective and curative effects.Actually, cisplatin contributed to various mechanisms of liver dysfunction consisting of cellular toxicity, vasoconstriction in the renalmicrovasculature, and proinflammatory effects, by producing free radical oxidative stress, which participated in the decline ofantioxidant enzymes in the liver and led to liver injury. Hence, the possible mechanism of hepatoprotection and curative effect ofFicus glomerata supplement could be due to its good antioxidant potential content; it might contribute to free radical scavenging andantagonistic hepatotoxicity that were produced by cisplatin in liver injury.